Evaluating Teachers’ Assessment Practice on Students Writing Performance - Nia Pujiawati (Journal of English Language Studies, 2019)
Teachers’ writing assessment practice in foreign language learning classroom is the issue that has not been investigated empirically and rigorously. Bearing this fact in mind, this study looks at how teachers gauge students’ conceptual understanding and ability to perform task. To this end, four English teachers who had the experience of writing instruction and assessment in their classroom were interviewed, and twenty students were also cross-examined to ensure the trustworthiness. The data analysis reveals that the teachers’ assessment practice does not meet the expectations and the standards. The students involved, moreover, specified that the teachers only showed them the score without giving a further explanation on their strengths and weaknesses, and they never indicated which part the students have gone wrong in their written work. Therefore, the results suggest the stakeholder to give the teachers professional development by training them with the fundamental knowledge base for carrying out valid assessment in any context.Keywords: evaluation, teacher’s assessment, writing